PENGARUH TERPAAN TAYANGAN “86” DI NET. TV TERHADAP PERSEPSI KHALAYAK DI KOTA DENPASAR TENTANG POLRI - Febriana, Ruth; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT The police in Indonesia are known as Polri or Kepolisian Negara Republik Indonesia. As law enforcer, the police is the most respected profession of the community. But in fact, when the police are on duty, instead received a lot of negative stigma from the wide community for several reasons. As if responding to these problems, NET. TV collaborated with Polri to produce television program which showing police actions and other information about the humanist side of the police entitled “86”. This study aims to see how television as a mass media that has the most dominant power in influencing the perception of its audience. The purpose of this research is to know the effect of “86” program on NET. TV toward perception of audience in Denpasar city about Polri.  This study applies quantitative research method in the form of explanative survey. This survey uses 120 sampels in Denpasar city to be used as research respondents. This research was used purposive sampling as the technique. The data analysis technique used is a simple linier regression test that is proscessed using computational calculation SPSS 23 program. The results showed that exposure of “86” program on NET. TV has a positive impact significanlty toward perception of audience in Denpasar city about Polri. That means when exposure of “86” program on NET. TV increasing, the perception of audience in Denpasar city about Polri will be better. Keywords : Audience, Indonesian National Police, Perception, Exposure to Television Media Program,Uses and Effect Mass Media